2014
DOI: 10.1093/jac/dku372
|View full text |Cite
|
Sign up to set email alerts
|

Transmitted HIV drug resistance in antiretroviral-treatment-naive patients from Poland differs by transmission category and subtype

Abstract: Despite stable trends over time, patterns of t-DRMs differed notably between transmission categories and subtypes: subtype B was associated with MSM transmission and clustering while in non-B clades t-DRMs were more common and were associated with heterosexual infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
5
12
1
Order By: Relevance
“…These findings suggested that genotype C was the dominant strain which was resistant to ART drugs. These results, showing more TDR in subtype C and no PI or NRTI TDR in subtype B, differ from previous studies in China [6,7] and worldwide [8][9][10][11]. However, in particular, there are reasons why our results for subtype C may be different from other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings suggested that genotype C was the dominant strain which was resistant to ART drugs. These results, showing more TDR in subtype C and no PI or NRTI TDR in subtype B, differ from previous studies in China [6,7] and worldwide [8][9][10][11]. However, in particular, there are reasons why our results for subtype C may be different from other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast, the CRF17_BF cluster has been characterized by HIV-1 strains resistant to both first and second NNRTIs generations, due to the presence of the RT mutations K101E and E138K [ 47 ]. These mutations are rarely found in drug-naïve HIV infected patients (prevalence: <0.4% for both non-B and B subtypes strains) [ 48 ], but were selected in a high proportion of patients receiving NNRTIs [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of TDR in treatment-naive individuals remains stable in most developed countries and the prevalence of acquired drug resistance is decreasing [22][23][24][25][26][27][28][29] . This implies that further transmission of HIV-1 with TDRMs is occurring in ART-naive individuals [6][7][8] .…”
Section: Drug Class Mutations Resistance Interpretationmentioning
confidence: 99%